Quantitative acetylated proteomics on left atrial appendage tissues revealed atrial energy metabolism and contraction status in patients with valvular heart disease with atrial fibrillation - Tu, Tao; Qin, Fen; Bai, Fan; Xiao, Yichao; Ma, Yingxu; Li, Biao; Liu, Na; Zhang, Baojian; Sun, Chao; Liao, Xiaobo; Zhou, Shenghua; Liu, Qiming (Frontiers in Cardiovascular Medicine, 2022)
Background Numerous basic studies have demonstrated critical roles of metabolic and contractile remodeling in pathophysiological changes of atrial fibrillation (AF), but acetylation changes underlying atrial remodeling have not been fully elucidated. Quantitative acetylated proteomics enables researchers to identify a comprehensive map of protein alterations responsible for pathological development and progression of AF in the heart of patients. Materials and methods In this study, 18 samples (9 with chronic AF and 9 with sinus rhythm) of left atrial appendage (LAA) tissues were obtained during mitral valve replacement surgery. Changes in the quantitative acetylated proteome between the AF and sinus rhythm (SR) groups were studied by dimethyl labeling, acetylation affinity enrichment, and high-performance liquid chromatography-tandem mass spectrometry analysis. Results We identified a total of 5,007 acetylated sites on 1,330 acetylated proteins, among which 352 acetylated sites on 193 acetylated proteins were differentially expressed between the AF and SR groups by setting a quantification ratio of 1.3 for threshold value and P < 0.05 for significant statistical difference. The bioinformatics analysis showed that the differentially expressed acetylated proteins were mainly involved in energy metabolism and cellular contraction and structure function-related biological processes and pathways. Among 87 differentially expressed energy metabolism acetylated proteins related to the processes of fatty acid, carbohydrate, ketone body metabolism, and oxidative phosphorylation, nearly 87.1% Kac sites were upregulated (148 Kac sites among 170) in the AF group. Besides, generally declining acetylation of cardiac muscle contraction-related proteins (88.9% Kac sites of myosin) was found in the LAA of patients with AF. Immune coprecipitation combined with Western blotting was conducted to validate the differential expression of acetylated proteins. Conclusion Many differentially expressed energy metabolism and cellular contraction acetylated proteins were found in the LAA tissues of patients with chronic AF, and may reflect the impaired ATP production capacity and decreased atrial muscle contractility in the atrium during AF. Thus, acetylation may play an important regulatory role in metabolic and contractile remodeling of the atrium during AF. Moreover, the identified new acetylated sites and proteins may become promising targets for prevention and treatment of AF.